The Effect Of Digital Content Marketing, E-WOM And Viral Marketing On The Interest Of Domestic Tourist Visits With Virtual Emotional Engagement As An Intervening Variable - Resti Nursabilla; Ramadania Ramadania; Wenny Pebrianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Digital Content Marketing, electronic word of mouth (E-WOM), and Viral Marketing on the interest of domestic tourist visits in Indonesia with Virtual Emotional Engagement as an intervening variable. The research method uses quantitative approach with SEM-PLS analysis. The Data was collected from 200 active respondents of Tiktok users. The results showed that Digital Content Marketing, E-WOM, and Viral Marketing had a positive and significant effect on Virtual Emotional Engagement, which in turn also significantly influenced the interest of domestic tourist visits. However, the direct influence of E-WOM on the interest of domestic tourist visits is not significant, but E-WOM is more effective in creating emotional engagement, which can ultimately increase the interest of domestic tourist visits indirectly. This finding confirms the importance of social media-based digital marketing strategies to increase the attractiveness of domestic tourist destinations in the digital age. In addition, this study makes a theoretical contribution to understanding the role of emotional engagement in virtual environments as a link between marketing strategies and tourist behavior.